Income redistribution is not enough: income inequality, social welfare programs, and achieving equity in health. Issue 12 (13th November 2007) - Starfield, Barbara; Birn, Anne-Emanuelle
Abstract : Income inequality is widely assumed to be a major contributor to poorer health at national and subnational levels. According to this assumption, the most appropriate policy strategy to improve equity in health is income redistribution. This paper considers reasons why tackling income inequality alone could be an inadequate approach to reducing differences in health across social classes and other population subgroups, and makes the case that universal social programs are critical to reducing inequities in health. A health system oriented around a strong primary care base is an example of such a strategy.